The chemical and biological properties of Fusarin C, a secondary mutagenic metabolite produced by Fusarium moniliforme Sheldon - Gelderblom, Wentzel Christoffel Andreas (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.(Agric.)) -- University of Stellenbosch, 1986.